(untitled) (Research, Society and Development, 2022)
This study analyzed indications and transfusion adverse events that occurred at Clemente Faria University Hospital, located in Montes Claros/MG. This was a cross-sectional, retrospective, quantitative and descriptive study. Data were collected from medical records, cross-testing sector records, and transfusion adverse events notification forms. The research was approved by the CEP of UNIMONTES. From 11/2018 to 06/2019, 1592 blood products were transfused at the HUCF, 54,6% packed red blood cells, 34,2% platelets, 7,9% fresh frozen plasma, and 3.3% cryoprecipitate. Among the packed red blood cells transfused, 5.4% were leukocyte-depleted, 6.9% were irradiated/deleukocyted, and 2.4% were leukocyte/phenotyped. Thirteen immediate adverse events were reported corresponding to 12.4/1000 transfusions performed. The classification of reactions was distributed into 8 non-hemolytic febrile reactions (mild), 2 allergic (mild), 1 TRALI- unlikely (severe), 1 transfusion-associated dyspnea- unlikely (moderate), and 1 other-related acute pain (mild). RBC concentrates were the most related adverse reactions (10/13), followed by platelets (3/10). The expected parameters as per the hemovigilance report (2016) define the average of 5 reactions/ 1000 transfusions performed. Published papers have demonstrated varied frequencies. No late adverse events were identified. Despite the existence of standardized procedures and evidence of periodic training, it is believed that there is underreporting of transfusion adverse events. We conclude that transfusion therapy requires well-defined training and procedures, in addition to hemovigilance and adverse event reporting.